The what works centres : lessons and insights from an evidence movement - Sanders, Michael; Breckon, Jonathan (Book collections on Project MUSE., 2023)
Leaders, researchers and practitioners from the UK ""What Works Network"" share their insights on the successes, failures, and future of the What Works Centres, which have proven successful and popular across a number of policy settings.